2010
DOI: 10.1074/jbc.m110.113647
|View full text |Cite
|
Sign up to set email alerts
|

The PRiMA-linked Cholinesterase Tetramers Are Assembled from Homodimers

Abstract: Acetylcholinesterase (AChE) is anchored onto cell membranes by the transmembrane protein PRiMA (proline-rich membrane anchor) as a tetrameric globular form that is prominently expressed in vertebrate brain. In parallel, the PRiMAlinked tetrameric butyrylcholinesterase (BChE) is also found in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…4C). Light dimers (no PRiMA), heavy dimers (with PRiMA), and tetramers (with PRiMA) were observed in the G 4 -enriched fractions, as reported previously (21). We obtained identical results in the case of AChE T N296Q/N381Q/N495Q , which suggested the oligomerization of AChE dimer or tetramer was not affected by the glycosylation of AChE T .…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…4C). Light dimers (no PRiMA), heavy dimers (with PRiMA), and tetramers (with PRiMA) were observed in the G 4 -enriched fractions, as reported previously (21). We obtained identical results in the case of AChE T N296Q/N381Q/N495Q , which suggested the oligomerization of AChE dimer or tetramer was not affected by the glycosylation of AChE T .…”
Section: Resultssupporting
confidence: 77%
“…We have shown that mammalian and chicken AChE T subunits can form mixed AChE T dimers or tetramers, in agreement with the notion that this association depends on the "four-helixbundle" contact between two catalytic domains (21). To investigate whether glycosylated and un-glycosylated AChE T subunits possess the same capacity for dimeric or AChE T N296Q/N381Q/N495Q and PRiMA-HA.…”
Section: Formation Of Interspecies Chicken-human Ache G 4 Hybrids-mentioning
confidence: 96%
See 3 more Smart Citations